The impact of fenugreek, black cumin, and garlic on dough rheology, bread quality, antimicrobial activity, and microstructural analysis using a scanning electron microscope - Zerlasht, Mehwish; Javaria, Sadaf; Quddoos, Muhammad Yousaf; Arshad, Rizwan; Yaqub, Shazia; Zubair Khalid, Muhammad; Sana Mahmood, Sayyad; Rafique, Ayesha; Umar Farooq, Muhammad; Alsulami, Tawfiq; Akram, Saima; Rafique, Hamad (Italian Journal of Food Science, 2024)
Fenugreek, black cumin, and garlic are herbs that are rich sources of antimicrobial and nutritional bioactive compounds. This study investigated the influence of herbs on the rheological characteristics of dough and the quality parameters of bread. The antimicrobial activity of the herbs was determined against the pathogens at 50 and 100 mg/mL concentrations. Maximum zone inhibition was measured for fenugreek against Salmonella typhimurium (16.5 mm) at 100 mg/mL concentration. Dough development time and departure time increased with the increase in concentration of the herbs. Farinograph quality number (FQN), mixing tolerance index, and stability varied significantly with the treatments such as physio-chemical, structural, textural, and sensory parameters at herbs concentration 0.25, 0.5, and 0.75%, respectively. Ash, fiber, fat, protein content, firmness, and total phenolic content were increased with treatments. However, a decrease in moisture content and total plate count was observed due to the addition of herbs. The microstructure revealed that the addition of fenugreek significantly improves the bread structure. The sensory profile of bread was not affected with the addition of herbs at a concentration of 0.50%.